3D visualization and modeling in the surgical treatment and postoperative management of hypertrophic obstructive cardiomyopathy: a case report - Uladzimir Andrushchuk; Marta Garbowska; Tomasz Chrostowski; Darya Andrushchuk; Wiktoria Dzieżyk; Dorota Sulima; Annet Litvinenko; Miłosz Nesterowicz (3D Printing in Medicine, 2026)
Abstract Background Three-dimensional (3D) visualization, modeling, and printing can enhance planning for septal myectomy in hypertrophic obstructive cardiomyopathy; however, their role in postoperative decision-making is less well defined. Case presentation A 49-year-old man underwent extended septal myectomy planned using cardiac computed tomography angiography (CTA)–based 3D modeling and virtual myectomy; patient-specific 3D-printed models processed using hydrogen peroxide plasma were used intraoperatively to guide resection. Intraoperative echocardiography confirmed relief of obstruction with resolution of systolic anterior motion (SAM) and a low residual left ventricular outflow tract (LVOT) gradient (6 mmHg). On postoperative day 3, dyspnea recurred with severe LVOT obstruction (peak gradient of 73 mmHg) and SAM. Repeat CTA and 3D modeling showed no residual anatomic septal substrate (maximal basal septal thickness of 15 mm), supporting a dynamic mechanism consistent with relative intravascular hypovolemia, tachycardia, and a hyperdynamic left ventricle. Hemodynamically targeted conservative management—preload augmentation, discontinuation of vasodilatory therapy, and intensified heart-rate control—normalized LVOT gradients (12 mmHg by postoperative day 7) and improved functional capacity. Conclusions This case report illustrates how repeated 3D assessment and printing can support effective surgical treatment in a patient with complex cardiac pathology and help avoid premature reintervention by excluding structural causes of early postoperative obstruction and guiding reversible, physiology-based management.